Analysis of Contractual Process of Users Committees: A Case of Khairahani Municipality, Chitwan, Nepal - Rajesh Koirala; A. K. Mishra; P. S. Aithal, (International Journal of Management, Technology and Social Sciences (IJMTS), 2022)
Purpose: The projects at local level in Nepal are found to be executed through users committee or contractors depending upon structure and budget. To assess the existing practice of formation & contractual process of Users Committees while implementing construction projects at Khairahani Municipality Chitwan., Nepal. Design/Methodology/Approach: The study was solely the project management practice of the Municipality implementing through UCs using Checklist Survey for projects with cost more than 10 laks. Data of the 33-sample site (different sectors of construction) will be collected and analyzed to obtain the significance. The information collected from the UCs members through the questionnaire and the consultations. The data were also collected from the Engineers, Sub Engineers, Planning officers, Assistant planning officer, Account Officer, Accountant, and elected representatives employed through questionnaire. All the collected data were analyzed quantitatively and qualitatively using bars, graphs & diagrams and comparison with existing laws. Findings/Result: The UCs in the projects of Municipality was formed by the general mass meeting of local beneficiaries without political interferences or biases. For the construction projects implementation through UCs, its formation was through the participatory approach but it was not strictly followed the prevailing acts, rules, guidelines and directives to local bodies for the composition of UCs. The supervision and monitoring mechanism exists but it was not functioning as well. The projects after the work completion had been examined and cleared within the time. The ownership of the projects, O & M fund and handover of the completed projects was not clearly defined. There were very few projects implemented through UCs that have adverse environmental impact, though the environmental impact consideration should be taken. From the study it is found that both the approaches can be suitable depending on the specific conditions and requirements. Each one of them has its own merits and demerits which do not enact in all situation of rural construction work. Originality/Value: The existing practice of formation and contractual process complies with existing laws, bylaws rules, regulations, and guidelines illustrate law binding nature. Paper Type: Research paper